1994
DOI: 10.1111/j.1439-0450.1994.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fimbrial and Toxin Genes in Escherichia coli and their Prevalence in Piglets with Diarrhoea. The Application of Colony Hybridization Assay, Polymerase Chain Reaction and Phenotypic Assays

Abstract: Two different genotypic methods, colony hybridization and polymerase chain reaction (PCR), were applied to detect enterotoxin, verotoxin and fimbrial genes in 708 Escherichia coli (E. coli) strains from piglets with diarrhoea. The results were compared with those obtained by phenotypic methods. D N A fragments specific for each of the enterotoxins LT, ST, and ST,, the verotoxins VT,, VT, and VT,,, and for each of the fimbrial genes K88 (F4), K99 (F5), 987P (F6), F41 and F107, respectively, were used as probes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 27 publications
5
51
0
Order By: Relevance
“…Several studies in many countries have reported that infection with ETEC carrying the F5, F6 or F41 fimbriae is agerelated, occurring in pigs less than 2 weeks of age (10,17,18). In this study we detected the genes for F5 (30%), F41 (32%) and F6 (25%), similarly these genes were found in 32%, 9.5% and 14.3% in the Minas Gerais State (14).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Several studies in many countries have reported that infection with ETEC carrying the F5, F6 or F41 fimbriae is agerelated, occurring in pigs less than 2 weeks of age (10,17,18). In this study we detected the genes for F5 (30%), F41 (32%) and F6 (25%), similarly these genes were found in 32%, 9.5% and 14.3% in the Minas Gerais State (14).…”
Section: Discussionsupporting
confidence: 50%
“…In ETEC strains, the fimbrial types F4 (K88) and F18 (F18ab, F18ac) are commonly found in pathogenic E. coli isolated from weaned pigs (4,18,25). There are also other fimbrial structures, such as F5 (K99), F6 (987P), F41, which are associated with porcine ETEC strains, but are more frequently associated with E. coli causing neonatal diarrhea (18,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR for fimbriae and enterotoxins was carried out as previously described with slight modification. 4,7,13 Bacterial DNA amplification was performed using 5 l of the supernatant of lysed bacteria, 90 ng of oligonucleotide primers, 0.2 mM each of dATP, dGTP, dCTP, and dTTP, 10 mM Tris HCl (pH 8.8), 1.5 mM MgCl 2 , 50 mM KCl, and 1 unit of Taq polymerase, a all in 50 l of distilled water. The PCR profile used included a denaturing step at 94 C for 1 min, followed by annealing of the primers at T1 for 2 min, with an extension step at 72 C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The STa primer sequence is (5'TCCGTGAAACAACATGACGG3', 5'ATAACATCCAGCA CAGGCAG3') and K99 primer sequence is (5'TGCGACTA CCAATGCTTCTG3', 5'TATCCACCATTAGACGGAGC3') [16,17]. A standard PCR protocol was adopted according to Salvadori et al [17].…”
Section: Purification and Characterization Of Native Sta From Etecmentioning
confidence: 99%